Direct arylation catalysis with chloro[8-(dimesitylboryl)quinoline-κN]copper(I) - Tamang, Sem Raj; Hoefelmeyer, James D. (Beilstein Journal of Organic Chemistry, 2016)
We report direct arylation of arylhalides with unactivated sp2 C–H bonds in benzene and naphthalene using a copper(I) catalyst featuring an ambiphilic ligand, (quinolin-8-yl)dimesitylborane. Direct arylation could be achieved with 0.2 mol % catalyst and 3 equivalents of base (KO(t-Bu)) at 80 °C to afford TON ≈160–190 over 40 hours.
Keywords: catalysis; C–C coupling; C–H activation; copper; direct arylation

Metal-catalyzed cross-coupling reactions - Diederich, F.; Stang, P. J. (Wiley VCH, 1998)

(untitled) - Negishi, E. (Angew. Chem., Int. Ed., 2011)

(untitled) - Suzuki, A. (Angew. Chem., Int. Ed., 2011)

(untitled) - Hassan, J.; Sévignon, M.; Gozzi, C.; Schulz, E.; Lemaire, M. (Chem. Rev., 2002)

(untitled) - Zhao, D.; You, J.; Hu, C. (Chem. – Eur. J., 2011)

(untitled) - Kuhl, N.; Hopkinson, M. N.; Wencel-Delord, J.; Glorius, F. (Angew. Chem., Int. Ed., 2012)

(untitled) - Cho, S. H.; Kim, J. Y.; Kwak, J.; Chang, S. (Chem. Soc. Rev., 2011)

(untitled) - Alberico, D.; Scott, M. E.; Lautens, M. (Chem. Rev., 2007)

(untitled) - McGlacken, G. P.; Bateman, L. M. (Chem. Soc. Rev., 2009)

(untitled) - Ackermann, L.; Vicente, R.; Kapdi, A. R. (Angew. Chem., Int. Ed., 2009)

(untitled) - Daugulis, O.; Do, H.-Q.; Shabashov, D. (Acc. Chem. Res., 2009)

(untitled) - Mousseau, J. J.; Charette, A. B. (Acc. Chem. Res., 2013)

(untitled) - Rossi, R.; Bellina, F.; Lessi, M.; Manzini, C. (Adv. Synth. Catal., 2014)

(untitled) - Ackermann, L.; Althammer, A.; Born, R. (Angew. Chem., Int. Ed., 2006)

(untitled) - Yang, S.-D.; Sun, C.-L.; Fang, Z.; Li, B.-J.; Li, Y.-Z.; Shi, Z.-J. (Angew. Chem., Int. Ed., 2008)

(untitled) - Seiple, I. B.; Su, S.; Rodriguez, R. A.; Gianatassio, R.; Fujiwara, Y.; Sobel, A. L.; Baran, P. S. (J. Am. Chem. Soc., 2010)

(untitled) - Nishikata, T.; Abela, A. R.; Huang, S.; Lipshutz, B. H. (J. Am. Chem. Soc., 2010)

(untitled) - Ban, I.; Sudo, T.; Taniguchi, T.; Itami, K. (Org. Lett., 2008)

(untitled) - Vogler, T.; Studer, A. (Org. Lett., 2008)

(untitled) - Wen, J.; Zhang, J.; Chen, S.-Y.; Li, J.; Yu, X.-Q. (Angew. Chem., Int. Ed., 2008)

(untitled) - Oi, S.; Fukita, S.; Inoue, Y. (Chem. Commun., 1998)

(untitled) - Hachiya, H.; Hirano, K.; Satoh, T.; Miura, M. (Angew. Chem., Int. Ed., 2010)

(untitled) - Phipps, R. J.; Gaunt, M. J. (Science, 2009)

(untitled) - Vallée, F.; Mousseau, J. J.; Charette, A. B. (J. Am. Chem. Soc., 2010)

(untitled) - Liu, W.; Cao, H.; Lei, A. (Angew. Chem., Int. Ed., 2010)

(untitled) - Liu, W.; Cao, H.; Xin, J.; Jin, L.; Lei, A. (Chem. – Eur. J., 2011)

(untitled) - Pieber, B.; Cantillo, D.; Kappe, C. O. (Chem. – Eur. J., 2012)

(untitled) - Chan, T. L.; To, C. T.; Liao, B.-S.; Liu, S.-T.; Chan, K. S. (Eur. J. Inorg. Chem., 2012)

(untitled) - Canivet, J.; Yamaguchi, J.; Ban, I.; Itami, K. (Org. Lett., 2009)

(untitled) - Kobayashi, O.; Uraguchi, D.; Yamakawa, T. (Org. Lett., 2009)

(untitled) - Yamaguchi, J.; Muto, K.; Itami, K. (Eur. J. Org. Chem., 2013)

(untitled) - Yamamoto, T.; Muto, K.; Komiyama, M.; Canivet, J.; Yamaguchi, J.; Itami, K. (Chem. – Eur. J., 2011)

(untitled) - Yokota, A.; Aihara, Y.; Chatani, N. (J. Org. Chem., 2014)

(untitled) - Do, H.-Q.; Daugulis, O. (J. Am. Chem. Soc., 2007)

(untitled) - Do, H.-Q.; Daugulis, O. (J. Am. Chem. Soc., 2008)

(untitled) - Yoshizumi, T.; Tsurugi, H.; Satoh, T.; Miura, M. (Tetrahedron Lett., 2008)

(untitled) - Liu, W.; Hou, F. (Appl. Organomet. Chem., 2015)

(untitled) - Liu, H.; Yin, B.; Gao, Z.; Li, Y.; Jiang, H. (Chem. Commun., 2012)

(untitled) - Yanagisawa, S.; Ueda, K.; Taniguchi, T.; Itami, K. (Org. Lett., 2008)

(untitled) - Shirakawa, E.; Itoh, K.-i.; Higashino, T.; Hayashi, T. (J. Am. Chem. Soc., 2010)

(untitled) - Liu, W.; Tian, F.; Wang, X.; Yu, H.; Bi, Y. (Chem. Commun., 2013)

(untitled) - Liu, W.; Xu, L.; Bi, Y. (RSC Adv., 2014)

(untitled) - Liu, W.; Xu, L. (Tetrahedron, 2015)

(untitled) - Wu, Y.; Choy, P. Y.; Kwong, F. Y. (Asian J. Org. Chem., 2014)

(untitled) - Wu, Y.; Choy, P. Y.; Kwong, F. Y. (Org. Biomol. Chem., 2014)

(untitled) - Dewanji, A.; Murarka, S.; Curran, D. P.; Studer, A. (Org. Lett., 2013)

(untitled) - Ng, Y. S.; Chan, C. S.; Chan, K. S. (Tetrahedron Lett., 2012)

(untitled) - Gai, L.; To, C. T.; Chan, K. S. (Tetrahedron Lett., 2014)

(untitled) - Bouhadir, G.; Bourissou, D. (Chem. Soc. Rev., 2016)

(untitled) - Son, J.-H.; Pudenz, M. A.; Hoefelmeyer, J. D. (Dalton Trans., 2010)

(untitled) - Tamang, S. R.; Hoefelmeyer, J. D. (Molecules, 2015)

(untitled) - Emslie, D. J. H.; Cowie, B. E.; Kolpin, K. B. (Dalton Trans., 2012)

(untitled) - Field, L. D.; Sternhell, S.; Wilton, H. V. (J. Chem. Educ., 1999)

(untitled) - Streitwieser, A., Jr; Lawler, R. G.; Perrin, C. (J. Am. Chem. Soc., 1965)

(untitled) - Sperotto, E.; van Klink, G. P. M.; van Koten, G.; de Vries, J. G. (Dalton Trans., 2010)

(untitled) - Sambiagio, C.; Marsden, S. P.; Blacker, A. J.; McGowan, P. C. (Chem. Soc. Rev., 2014)

(untitled) - Studer, A.; Curran, D. P. (Angew. Chem., Int. Ed., 2011)

(untitled) - Zhou, S.; Anderson, G. M.; Mondal, B.; Doni, E.; Ironmonger, V.; Kranz, M.; Tuttle, T.; Murphy, J. A. (Chem. Sci., 2014)

(untitled) - Patil, M. (J. Org. Chem., 2016)

(untitled) - Zhang, L.; Yang, H.; Jiao, L. (J. Am. Chem. Soc., 2016)

(untitled) - Drapeau, M. P.; Fabre, I.; Grimaud, L.; Ciofini, I.; Ollevier, T.; Taillefer, M. (Angew. Chem., Int. Ed., 2015)

(untitled) - Barham, J. P.; Coulthard, G.; Emery, K. J.; Doni, E.; Cumine, F.; Nocera, G.; John, M. P.; Berlouis, L. E. A.; McGuire, T.; Tuttle, T.; Murphy, J. A. (J. Am. Chem. Soc., 2016)

(untitled) - Wang, M.; Fan, T.; Lin, Z. (Organometallics, 2012)

(untitled) - Casitas, A.; Ribas, X. (Chem. Sci., 2013)

(untitled) - Ichiishi, N.; Canty, A. J.; Yates, B. F.; Sanford, M. S. (Organometallics, 2014)

(untitled) - Casitas, A.; Canta, M.; Solà, M.; Costas, M.; Ribas, X. (J. Am. Chem. Soc., 2011)

(untitled) - Casitas, A.; King, A. E.; Parella, T.; Costas, M.; Stahl, S. S.; Ribas, X. (Chem. Sci., 2010)

(untitled) - Bacon, R. G. R.; Hill, H. A. O. (J. Chem. Soc., 1964)

(untitled) - Litvak, V. V.; Shein, S. M. (Zh. Org. Khim., 1974)